2015
DOI: 10.4103/0971-5916.160698
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, vitamin D & diabetes risk-factors modified by a short-term yoga-based lifestyle intervention in overweight/obese individuals

Abstract: Background & objectives:Several diabetes prevention programmes have demonstrated a reduction in incidence of diabetes in individuals with prediabetes through weight loss. Short-term yoga-based lifestyle intervention programmes have also been shown to be efficacious in weight loss. This study was undertaken to investigate if interleukin (IL)-6, vitamin D, neopterin, vaspin, and diabetes risk factors can be modified by a short-term yoga-based lifestyle intervention in overweight/obese subjects.Methods:In this pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…All the six studies [ 29 , 32 , 34 , [36] , [37] , [38] ] reported a significant decrease in IL-6 levels, three studies [ 29 , 34 , 36 ] reported a significant reduction in TNF-alpha levels, and one study [ 32 ]reported an insignificant increase in TNF-alpha after 12-week yoga intervention. One study [ 39 ] reported a nonsignificant decrease in vaspin levels, one study [ 31 ] reported a significant reduction in chemerin, PAI-1, and visfatin levels, and one study reported a significant decrease in TGF-beta levels [ 34 ] following the yoga practice. [ Table 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…All the six studies [ 29 , 32 , 34 , [36] , [37] , [38] ] reported a significant decrease in IL-6 levels, three studies [ 29 , 34 , 36 ] reported a significant reduction in TNF-alpha levels, and one study [ 32 ]reported an insignificant increase in TNF-alpha after 12-week yoga intervention. One study [ 39 ] reported a nonsignificant decrease in vaspin levels, one study [ 31 ] reported a significant reduction in chemerin, PAI-1, and visfatin levels, and one study reported a significant decrease in TGF-beta levels [ 34 ] following the yoga practice. [ Table 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, the authors concluded that a short-term yoga-based lifestyle intervention favorably modified IL-6, vitamin D, and diabetes risk factors in obesity. 24 Finally, a study by Kanaya et al tested a restorative yoga intervention with active stretching for metabolic outcomes. For this purpose, the authors conducted a 48-week randomized trial comparing restorative Yoga and stretching among underactive adults with metabolic syndrome at the Universities of California, San Francisco, and San Diego.…”
Section: L80mentioning
confidence: 99%
“…Several studies in the prediabetic population show the effectiveness of yoga in reducing the risk of progression to diabetic state. [3336] There is not a single review to show the benefits of yoga in prediabetes. This will be the 1st systematic review that will show evidence that yoga significantly affects the prediabetic state and will summarize the results of these available studies.…”
Section: Rationalementioning
confidence: 99%